2022
DOI: 10.1089/ars.2021.0038
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-Interacting Protein in Cancer and Diabetes

Abstract: Significance: Thioredoxin interacting protein (Txnip) is an α-arrestin protein that acts as a cancer suppressor. Txnip is simultaneously a critical regulator of energy metabolism. Other alpha-arrestin proteins also play key roles in cell biology and cancer.Recent Advances: Txnip expression is regulated by multi-layered mechanisms including transcriptional regulation, microRNA, mRNA stabilization and protein degradation. The Txnip-based connection between cancer and metabolism has been widely recognized.Meanwhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 196 publications
(332 reference statements)
0
21
0
Order By: Relevance
“…AP is an unpredictable and potentially lethal disease [32]. In this study, we demonstrated, for the first time, that GSDMD was overexpressed in the ER of acinar cells, which exacerbated AP by the TXNIP/HIF-1α pathway.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…AP is an unpredictable and potentially lethal disease [32]. In this study, we demonstrated, for the first time, that GSDMD was overexpressed in the ER of acinar cells, which exacerbated AP by the TXNIP/HIF-1α pathway.…”
Section: Discussionmentioning
confidence: 59%
“…Meanwhile, DSF significantly downregulated the level of GSDMD in the ER (Figure 2hi-iii). TXNIP is related to ROS bursts in cells, which meditates ERS [14,32]. A study revealed that the accumulation of GSDMD in the mitochondria increases cytochrome C release by increasing mitochondrial permeability [14], which may lead to an increase in ROS.…”
Section: Inhibition Of Gsdmd Accumulation In Endoplasmic Reticulum Am...mentioning
confidence: 99%
“…Many studies have demonstrated that Txnip comprises a major tumor suppressor that inhibits the proliferation of tumor cells (31,40,43,44,45,46) were significantly increased after 12 weeks of HFD. Thus, our results suggest that Txnip deficiency can promote pancreatic β cell proliferation in HFD-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Txnip is a multifunctional protein that is ubiquitously expressed and is localized in the nucleus, mitochondria and cytoplasm. It is associated with the development of diabetes, cardiovascular disease, central nervous system diseases, cancer and other diseases (29,30,31). Recently, Txnip has been the focus of investigation due to its unique characteristic of specifically binding and regulation of Trx activity (32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation